Chronic Drug-Induced Liver Injury from Labetalol during the Postpartum Period: A Case Report - Lee, Bruce; Xiong, Suriya; Westen, Elizabeth A.; Warner, Julie Ann (American Journal of Perinatology Reports, 2024)
Drug-induced liver injury (DILI) is a common cause of transaminitis in pregnancy. A 34-year-old G3P2012 presented 3 weeks postpartum for preeclampsia with severe features. After receiving acute antihypertensive medications, she was discharged home with labetalol. She presented 5 months later with general malaise, scleral icterus, nausea, and mild right upper quadrant pain and found to have significantly elevated transaminitis. She had a negative infectious, autoimmune, biliary, and steatohepatitis workup. A liver biopsy was performed supporting the diagnosis of DILI. After patient self-discontinued labetalol, her hepatitis significantly improved. However, she developed chronic DILI and liver enzymes normalized during her subsequent pregnancy at 34 weeks. Patient's written consent was obtained for this case report. Chronic DILI secondary to labetalol use is a rare and potentially fatal condition that should be considered on the differential for transaminitis during pregnancy and postpartum period.
Keywords: drug-induced liver injury; labetalol; preeclampsia; postpartum; transaminitis